Pengaruh penambahan brokoli terhadap daya terima dan kadar vitamin C pada dimsum ayam - Alfi Tiarisma; Abdul Hadi (Poltekkes Kemenkes Aceh, 2025)
Background: Dimsum contains nutrients such as high protein because the main ingredients for making dimsum come from animals, but low fiber and vitamin content. Broccoli as a local food can be utilized to add nutritional content such as vitamin C, etc. to dimsum.Objective: To determine the effect of broccoli addition on the acceptability and vitamin C content of chicken dim sum.Methods: This study is an experimental study using non factorial completely randomized design. The variables studied in this study were the chemical test of vitamin C using the iodometric method at the Faculty of Agriculture Laboratory, Syiah Kuala University and the organoleptic test by 30 panelists conducted at the Food Technology Laboratory of the Poltekkes Kemenkes Aceh on April 26, 2024. The data obtained were analyzed by ANOVA test. If there is a significant difference between treatments, it is continued with the Duncan test.Results: The addition of broccoli has an effect on taste (P = 0,004), texture (p = 0,009), and vitamin C content (p = 0,000). However, it has no effect on aroma (p = 0,681) and color (p = 0,092). Therefore, the results of the Duncan test on taste are not significantly different. the results of the Duncan test on the texture of F1 and F2 dimsum are not significantly different, in F2 and F3 are significantly different. In F1 and F3 significantly different. The results of the duncan test on vitamin C are significantly different.Conclusion: The addition of broccoli in dimsum has a significant effect on taste, texture, and vitamin C but has no effect on aroma and color.